2018
DOI: 10.1159/000491470
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the FKBP25-60S Ribosomal Protein L7a Stress Response Signaling During Ischemic Injury

Abstract: Background/Aims: Peptidyl-prolyl cis-trans isomerase FKBP25 is a member of the FK506-binding proteins family which has peptidyl-prolyl cis/trans isomerase domain. The biological function and pathophysiologic role of FKBP25 remain elusive. Methods: The spatio-temporal changes in expression of endothelial FKBP25 upon oxygen-glucose deprivation (OGD) treatment were examined by Western blot and immunofluorescence. The immunoprecipitation and fluorescence resonance energy transfer (FRET) were used to address the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This helix bundle domain was found to mediate protein-protein interaction for ubiquitination and therefore degradation of oncogene mouse double minute 2 (MDM2), which leads to an enhanced expression of tumor suppressor protein p53 (Ochocka et al, 2009). Recently, interaction with double-stranded RNA (dsRNA) (Dilworth et al, 2017) and a role in ischemia stress injury protection (Jiang et al, 2018) were disclosed.…”
Section: Fkbp25mentioning
confidence: 99%
“…This helix bundle domain was found to mediate protein-protein interaction for ubiquitination and therefore degradation of oncogene mouse double minute 2 (MDM2), which leads to an enhanced expression of tumor suppressor protein p53 (Ochocka et al, 2009). Recently, interaction with double-stranded RNA (dsRNA) (Dilworth et al, 2017) and a role in ischemia stress injury protection (Jiang et al, 2018) were disclosed.…”
Section: Fkbp25mentioning
confidence: 99%
“…Because the mRNA translation is controlled by 80S formation and 60S availability 54 and the nucleolar hypertrophy is an indicator of ribosome biogenesis, 55 the rpL7a was an appropriate choice. In addition, rpL7a is a highly conserved ribosome protein localized on the surface of the 60S 56 , 57 and contains two distinct RNA binding domains 58 and an FKBP25 binding domain, 59 suggesting that rpL7a may play an essential role in 60S subunit biogenesis. Notably, the localization of rpL7a on the surface of the 60S ribosomal subunit enables the use of rpL7a as a readout for the ribosomal large subunit biogenesis and protein expression.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies on the expression of the L7A protein in various pathologies have been carried out. An increase in the expression of this ribosomal protein was observed during the adaptation reaction to trauma associated with ischemic disease [12,16]. There are also studies that have shown an increase in the L7A concentration in prostate carcinoma and colorectal carcinoma [27][28][29].…”
Section: Area Of Mitochondrial Staining With Mitotracker Red and The ...mentioning
confidence: 94%
“…Studies of lymphoid tissue with aging show the development of a progressively decreasing mitochondrial respiratory function due to a decrease in the mitochondrial membrane potential and impaired mitophagy [12]. The production of ATP decreases as a result of the violation of oxidative phosphorylation.…”
Section: Area Of Mitochondrial Mitotracker Red Staining and The Expre...mentioning
confidence: 99%